ANALISIS DAMPAK SOSIAL PEMBANGUNAN JALAN DI DUSUN JATAK KECAMATAN MENYUKE KABUPATEN LANDAK - Jasupa, Agustin; Zakso, Amrazi; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstrackThe title of this thesis Social Impact Of Street Construction In Jatak Village Menyuke Subdistrict Landak Regency. The problem in this research is How is the Social Impact Of Street Construction Analysis In Jatak Village Menyuke Subdistrict Landak Regency. The sub-problem in this research was how in social interaction of associative in the form of cooperation of road construction and How is the positive impact posed by the construction roads in Jatak sub-district of Menyuke Landak Regency.The purpose of this study is to describe the social impact of the development of roads in Jatak Hamlet Subdistrict Menyuke Landak District. . Research study qualitative approach by using descriptive method was used in . Data collecting technique through observation, interviews, and documentation. The result of the research shows that: The associative social interaction of cooperation form the existence of road construction is: The form of cooperation is by mutual cooperation, which in mutual cooperation need to blend role reach the common goal such as; religious social activities that can generate cooperation between elements of society to succeed implementation these activities. Positive impacts caused by the construction of roads are Can enjoy various advances in various fields of life, be it social, economic. Keywords: Social Impact, Social Interaction